Effects of Baby Massage on Weight Gain in Babies - Susi Hartati; Desmariyenti D; Nurul Hidayah (Science Midwifery, 2020)
Massage is stimulation of the skin and tissues below it with various levels of hand pressure to reduce pain, make reflexes and improve circulation and have biochemical and psychological effects on the body. Stimulant massage for a term baby can improve the relationship between baby and mother and can increase body weight in baby.But unfortunately there are still many myths in the community, especially in the care of babies who are still believed that babies should not be massaged often, their bodies are still weak or other reasons that have never been verified. Though touching the baby at the beginning of his birth can have a positive influence on the growth of the baby. This study aims tothe effect of baby massage on the increase of baby weight in the work area at pekanbaru payung sekaki primary health center in 2019. This study used a Quasi Experiment design with Cross Sectional research design. Samples taken as many as 20 babies, 10 babies carried out baby massage and 10 other babies were not carried out baby massage. Sampling technique for consecutive sampling. The data collection tool uses checklist sheets, baby massage SOP, and baby scales. Data analysis was used univariate and bivariate, with statistical tests namely non-parental and Mann Whitney tests with the help of SPSS. The results showed that the p-value < 0.05. This means that 0,000<0,05, means that there is the effect of baby massage on the increase in baby massage weight in the work area at Payung Sekaki Pekanbaru Health Center in 2019. It is expected that the Payung Sekaki Pekanbaru health center Primary can conduct counseling or do baby massage to the local community